a) 1/3x - 2 = x + 2 / +2
1/3x = x + 4 / *3
x = 3x + 12 / -3x
-2x = 12 / :(-2)
x = -6
b) 1 - 6/7x = 4/7 / *7
7 - 6x = 4 / -7
-6x = -3 / :(-6)
x = 1/2
c) 6(1/4x - 2) = 18 / :6
1/4x - 2 = 3 / +2
1/4x = 5 / *4
x = 20
d) x/6 - 1/6 = 1 / * 6
x - 1 = 6 / + 1
x = 7
e) -2(2x-1) = x/3
-4x + 2 = x/3 / * 3
-12x + 6 = x / + 12x
6 = 13x / : 13
x = 6/13
f) 2/5(3-x) = -2 / * 5
2(3-x) = -10 / : 2
3 - x = -5 / - 3
-x = -8 / * (-1)
x = 8
g) 3/4(2-3x) = -6 / * 4
3(2-3x) = -24 / : 3
2-3x = -8 / -2
-3x = -10 / : (-3)
x = 10/3
h) 1/5(x-3) = 9 - x / *5
x - 3 = 45 - 5x / +5x
6x - 3 = 45 / +3
6x = 48 / :6
x = 8
i) (0,6+x)/2 = x + 1 / *2
0,6 + x = 2(x+1) / -0,6
x = 2x + 2 - 6/10 / -2x
-x = 20/10 - 6/10
-x = 14/10 / *(-1)
x = -1,4